A.A.T.E. Guide to English Books 1975 - Australian Association for the Teaching of English; Watson, Ken; Australian Association for the Teaching of English ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1975)
One in a series of annual publications, this booklet contains reviews of books relating to the teaching of English and the language arts. The books are divided into 11 categories: teaching principles and practice; composition, writing, rhetoric; source books and kits; books for the slower learner; prose; poetry; drama; language; literary criticism; mass media; and miscellaneous. Also included are an index of books reviewed (listed by title) and a list of the reviewers. (GW)
Availability: Australian Association for the Teaching of English, Inc., 163A Greenhill Road, Parkside, South Australia 5063 ($2.50).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Book Reviews; Drama; Educational Resources; Elementary Secondary Education; English Instruction; Foreign Countries; High Interest Low Vocabulary Books; Language; Language Arts; Literary Criticism; Mass Media; Poetry; Prose; Reading Materials; Slow Learners; Writing (Composition); Australia; Reference Materials, Bibliographies